Knowledge, Attitude, and Practice of Metformin Extended-Release Tablets Among Clinicians in China: A Cross-Sectional Survey - Liu, Chang; Tang, Siqi; An, Kang; Zhang, Shengzhao; Zhou, Yiling; Su, Na; Yang, Rong; Liao, Xiaoyang; An, Zhenmei; Li, Sheyu (Frontiers in Pharmacology, 2021)
Background Metformin extended-release (XR) is the once-daily alternative of the conventional immediate-release (IR) tablets for adults with type 2 diabetes. Aim To investigate the knowledge, attitude, and practice of the use of metformin XR tablets among clinicians. Methods We conducted a cross-sectional online survey among endocrinologists, general practitioners, and internists, who are taking routine care of adults with type 2 diabetes in health institutes at all levels in Sichuan Province, China. We designed an online questionnaire including the demographic information, the knowledge, attitude, and practice about metformin XR tablets. Results We included 158 clinicians, 67.7% of whom were females and 63.9% were from the tertiary hospitals. The median age was 39.6 years (ranged between 22 to 62 years). Only 8.2% of the clinicians correctly answered the knowledge questions, and 82.3% and 62.0% of the responders assumed that metformin XR had superior efficacy and tolerability to the metformin IR, respectively. Only 46.8% of the clinicians prescribed the metformin XR due to the adults’ preference for once daily frequency. Conclusion The knowledge, attitude and practice of the metformin XR among Chinese clinicians need improving. The clinicians need credible information to support their clinical decision-making regarding metformin XR.